The Routledge handbook of religions and global development - Tomalin, Emma (Routledge, 2015)
1. Introduction / Emma Tomalin -- 2. Development, religion and modernity / Carole Rakodi -- 3. Researching religions and development / Tara Hefferan -- 4. Theology and development : Christian and Jewish approaches / Stephen Plant and Daniel H. Weiss -- 5. A history of faith-based aid and development / Gregory Deacon and Emma Tomalin -- 6. Proselytizing development / Philip Fountain -- 7. Religion and development in Sub-Saharan Africa : an overview / Barbara Bompani -- 8. Pentecostalism and economic development in Sub-Saharan Africa / Dena Freeman -- 9. Masculinities, HIV and religion in Africa / Adriaan van Klinken and Ezra Chitando -- 10. Development and religious change in Latin America / Paul Freston -- 11. Inca roads, Protestant hospitals, Catholic cheese, and the fluctuating state : religion and development in Ecuador / Jill DeTemple -- 12. The Catholic Church, contemporary sexual politics and development in Latin America / Juan Marco Vaggione -- 13. Religion and development in India and Pakistan : an overview / Emma Tomalin -- 14. Caste and the conundrum of religion and development in India / David Mosse -- 15. Religion, gender and development in South Asia / Nida Kirmani and Tamsin Bradley -- 16. Religion and development in China / Andre Laliberte -- 17. Critical perspectives on religions : especially Christianity : in the development of South Korea post-1945 / Kirsteen Kim -- 18. Religion and gender in developing South-East Asia / Monica Lindberg Falk -- 19. Religion and development in the Middle East and North Africa (MENA) : poverty relief or social transformation? / Rana Jawad -- 20. Islamic finance, financial inclusion and poverty reduction in MENA / Amin Mohseni-Cheraghlou -- 21. Sexuality, development and Islamophilia in the Arab uprisings : the missing links Mariz Tadros -- 22. Faith-based organizations and development / Laurie A. Occhipinti -- 23. Religion at the intersection of development and public health in development contexts : from advocacy about faith-based organizations to systems thinking / Jill Olivier -- 24. Conflict or compatibility? Reflections on the nexus between human rights, development and religion in Muslim aid organizations / Marie Juul Petersen -- 25. Complex global institutions : religious engagement in development / Katherine Marshall -- 26. Sustainable development, climate change and religion / Sigurd Bergmann -- 27. Religion and economic development / Daromir Rudnyckyj -- 28. Religion, development, and fragile states / Seth D. Kaplan -- 29. Development organizations' support for faith-based education : recent turns toward ethics and dialogue / Amy Stambach.